Library Management System Using Android - S. Sawant, S; Shirsat, H.R; Dalvi, S.S; Rane, P.S (International Journal of Computer Sciences and Engineering, 2020)
Today’s education institutes understand the importance of the library with the increase in education standards. Library management system is online system. This system helps in maintaining all daily tasks of library. As the numbers of users are increasing there is a demand for effective library management system that reduces cost of management and saves time of users. This project has facility of student login and a facility of teacher login which are generally not available in manual library management systems. It also has a feature of librarian login through which the librarian can handle the entire system .It also has a facility through which student can view list of issued book to them and its issued date and return date after logging in their accounts. Through feedback students can appeal librarian to add new books and can also give suggestions. This system also authenticates users through email verification.